¡Que viva la música! Repaso de conversación en español - Corrales-Martin, Norma (Open textbook library., 2021)
¡Qué viva la música! Repaso de conversación en español, or Long Live Music! Spanish Conversational Review is an open textbook intended for conversational review, typically a fourth-semester Spanish class. The textbook is organized around nine different songs that provide students opportunities to practice, aurally and orally, as well as in writing, the main communicative goals and key grammatical structures learned in previous classes. It can also be used in similar high school classes.